Clinical Characteristics of Autosomal Dominant GJA1 Missense Mutation Linked to Oculodentodigital Dysplasia in a Korean Family. Issue 4 (April 2019) - Park, Do Young; Cho, Sung Yoon; Jin, Dong-Kyu; Kee, Changwon
Abstract : Purpose: We aimed to present a comprehensive assessment of the ophthalmic characteristics of genetically confirmed oculodentodigital dysplasia (ODDD) in 4 members of a single Korean family across 3 generations. Patients and Methods: The characteristics of 4 affected ODDD patients were evaluated. Comprehensive ophthalmic and medical examinations were performed in 3 patients including the proband, together with genetic analysis, and retrospective chart review was conducted for an affected ancestor. For genetic analysis, targeted gene panel sequencing was conducted using genomic DNA extracted from peripheral blood. Results: All affected individuals in this family showed shared ophthalmic abnormalities of microcornea, microphthalmia, elevated intraocular pressure, and shallow anterior chamber, all of which have been reported as typical ocular features of ODDD. Myopic refractive error despite short axial length and thick cornea were highlighted as new findings of ODDD. Facial abnormalities were common in all affected members, but their fingers were normal. Severity of glaucoma was different among the affected individuals and seemed to depend on elevation of intraocular pressure, which occurred in narrow, but open-angle. Genetic analysis revealed the presence of c.119C>T (p.Ala40Val) in GJA1, which is responsible for ODDD, but not found in the control population. Conclusions: This report describes detailed ocular characteristics in a genetically confirmed ODDD family, including unreported findings of thick cornea and myopic refractive error despite short axial length. The ocular features derived from the A40V mutation in GJA1 showed complete penetrance, suggesting a possible role of Cx43 in regulation of IOP and pathogenesis of glaucoma.